Age-dependent divergent effects of OX40L treatment on the development of diabetes in NOD mice. (3rd July 2016) - Haddad, Christine S.; Bhattacharya, Palash; Alharshawi, Khaled; Marinelarena, Alejandra; Kumar, Prabhakaran; El-Sayed, Osama; Elshabrawy, Hatem A.; Epstein, Alan L.; Prabhakar, Bellur S.
Abstract: Earlier, we have shown that GM-CSF derived bone marrow (BM) dendritic cells (G-BMDCs) can expand Foxp3 + regulatory T-cells (Tregs) through a TCR-independent, but IL-2 dependent mechanism that required OX40L/OX40 interaction. While some reports have shown suppression of autoimmunity upon treatment with an OX40 agonist, others have shown exacerbation of autoimmune disease instead. To better understand the basis for these differing outcomes, we compared the effects of OX40L treatment in 6-week-old pre-diabetic and 12-week-old near diabetic NOD mice. Upon treatment with OX40L, 6-week-old NOD mice remained normoglycemic and showed a significant increase in Tregs in their spleen and lymph nodes, while 12-week-old NOD mice very rapidly developed hyperglycemia and failed to show Treg increase in spleen or LN. Interestingly, OX40L treatment increased Tregs in the thymus of both age groups. However, it induced Foxp3 + CD103 + CD38 − stable-phenotype Tregs in the thymus and reduced the frequency of autoreactive Teff cells in 6-week-old mice; while it induced Foxp3 + CD103 − CD38 + labile-phenotype Tregs in the thymus and increased autoreactive CD4 + T cells in the periphery of 12-week-old mice. This increase in autoreactive CD4 + T cells was likely due to either a poor suppressive function or conversion of labile Tregs into Teff cells. Using ex vivo cultures, we found that the reduction in Treg numbers in 12-week-old mice was likely due to IL-2 deficit, and their numbers could be increased upon addition of exogenous IL-2. The observed divergent effects of OX40L treatment were likely due to differences in the ability of 6- and 12-week-old NOD mice to produce IL-2.